India's trilemma: Financial liberalization, exchange rates and monetary policy - Michael M. Hutchison; Rajeswari Sengupta; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2010)
A key challenge for macroeconomic policy in open economies is how to simultaneously manage exchange rates, interest rates and capital account openness - the trilemma. This paper calculates a trilemma index for India and investigates its evolution over time. We find that financial integration has increased markedly after the mid-2000s, with corresponding limitations on monetary independence and exchange rate stability. This tradeoff has been mitigated, however, with the rise of international reserves as a partially independent instrument of macroeconomic policy. In addition, we confirm that the weighted sum of the three indexes adds up to a constant, validating the notion that a rise in one trilemma variable should be traded-off with a drop of the weighted sum of the other two. Finally, we consider the implications of changes in the trilemma index for macroeconomic outcomes. We find some evidence that greater financial integration and corresponding loss of monetary autonomy and exchange rate stability has influenced inflation and inflation volatility, though not in a consistent manner.
Keywords: E4; E5; F3; F4; 330; Financial trilemma; Indian economy; International reserves; Foreign exchange intervention; Monetary policy; Capital account opening.